New technologies in Polish commercial arbitration on the background of European Union regulations - Ryszkowski, Karol (Review of European and Comparative Law, 2022)
Commercial arbitration in Poland has to face contemporary problems, including those related to the constant development of information technologies, and therefore new technologies. It is seen during the COVID pandemic. This article is intended to assess the state of Polish regulation on the background of European Union regulations in the abovementioned area and to propose potential changes to the Polish legislation[1] if they are needed. [1] Karol Ryszkowski, “New technologies in the Polish commercial arbitration,” in Právo, obchod, ekonomika : zborník príspevkov (Právo - obchod - ekonomika), eds. Jozef Suchoža, Ján Husár, and Regina Hučková (Košice: Univerzita Pavla Jozefa Šafárika Vydavatel’stvo Šafárik Press, 2020), 249.